THE EFFECTS OF FDI AND ECONOMIC GROWTH ON CO2 EMISSIONS IN SADC - Gule, Luciano (PEOPLE: International Journal of Social Sciences, 2021)
This study investigates the effects of foreign direct investment (FDI), economic growth, and capital stocks on the CO2 emissions in 16 Southern African Development Community (SADC). The analysis includes panel data from 1990 to 2014. To examine the effect, both statics and dynamics estimation models were used in this research. The results from panel statics using pooled ordinary least square and dynamic panel estimation using system general methods of the moments suggest a positive and significant effect of FDI and economic growth on CO2 emissions in SADC. While in contrast, capital stocks have negative and significant effects on CO2. These results indicate that FDI inflow has been damaging the environment in SADC countries. While when investing in clean energy the CO2 emissions tend to reduce. Hence, these countries should adopt policies that encourage the use of environmentally friendly technology and keep pursuing sustainable development goals while protecting the environment.